Ujawnienie i prezentacja informacji sprawozdawczej w stowarzyszeniach - Taracińska, Lilianna (Disclosure and Presentation of Reporting Information in Associations, 2007)
Lack of explicit guideline on reporting information disclosure is a reason for discrepant accuracy level in revealed information in notes to the financial statements. In the case of non-profit organizations, it has particular meaning. Such organizations should be characterized by clarity of information. Unfortunately they aren't. Additionally, there are no legal obligation for them to prepare management report. It causes that financial statement is less clear. Thought, some associations that are not into business prepare such report. In most cases it contains exclusively itemized list of organized trainings, collections, etc.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 158-162